Efficacy of the Natural Clay, Calcium Aluminosilicate Anti-Diarrheal, in Reducing Medullary Thyroid Cancer–Related Diarrhea and Its Effects on Quality of Life: A Pilot Study - Dadu, Ramona (Thyroid, 2015)
Introduction: Medullary thyroid cancer (MTC)–related diarrhea can be debilitating, reduces quality of life (QOL), and may be the only indication for initiating systemic therapy. Conventional antidiarrheal drugs are not always helpful and may have side effects. Calcium aluminosilicate antidiarrheal (CASAD), a natural calcium montmorrilonite clay, safely adsorbs toxins and inflammatory proteins associated with diarrhea. It was hypothesized that CASAD would reduce the severity of diarrhea and improve QOL in MTC patients. Methods: This was a prospective pilot trial (NCT01739634) of MTC patients not on systemic therapy with self-reported diarrhea of three or more bowel movements (BMs) per day for a week or more. The study design included a one-week run-in period followed by one week of CASAD ± a two-week optional continuation period. The primary endpoint was efficacy of one week of CASAD treatment in decreasing the number of BMs per day by ≥20% when compared with the baseline run-in period. Secondary objectives included tolerability and safety and the impact on QOL using the MD Anderson Symptom Inventory-Thyroid questionnaire (MDASI-THY). Results: Ten MTC patients (median age = 52 years, 70% female, 80% white) were enrolled. All had distant metastases, and median calcitonin was 5088 ng/mL (range 1817–42,007 ng/mL). Ninety percent had received prior antidiarrheals, and 40% of these had used two or more drugs, including tincture of opium (30%), loperamide (50%), diphenoxylate/atropine (20%), colestipol (10%), or cholestyramine (10%). Of seven evaluable patients, four (56%) had ≥20% reduction in BMs per day. Six out of seven patients discontinued their prior antidiarrheals. Best response ranged from 7% to 99% reduction in mean BMs/day from baseline. Five out of seven patients considered CASAD a success, and they opted for the two-week continuation period. Improvements in diarrhea and all six interference items assessed by MDASI-THY were noted at weeks 1 and 3. Total interference score was significantly improved at three weeks compared with baseline (p = 0.05). An oral levothyroxine absorption test was performed in one patient; malabsorption of levothyroxine was not observed. Adverse events included flatulence (40%), bloating (10%), heartburn (10%), and constipation (10%). Conclusions: CASAD is a promising strategy for treatment of MTC-related diarrhea. In this small pilot study, improvements in frequency and quality of diarrhea as well as QOL were noted. Further studies in this population are warranted.